Fabrication of dual heteroatom-doped graphitic carbon from waste sponge with “killing two birds with one stone” strategy for advanced aqueous zinc–ion hybrid capacitors - Li, Heng-Xiang; Shi, Wen-Jing; Liu, Ling-Yang; Zhang, Xiaohua; Zhang, Peng-Fang; Zhai, Yan-Jun; Wang, Zhao-Yang; Liu, Ying (Journal of colloid and interface science, 2023)
The N, S dual-doped porous graphitic carbon materials with the high graphitization degree were synthesized from the light fraction of coal tar pitch and waste sponge through a facile “killing two birds with one stone” process. The suitable N and S doping not only can provide extra electroactive sites, but also can improve the storage capacity of Zn ions through the decrease in Ea value for LC-750 cathode. [Display omitted] •The N, S dual-doped porous graphitic carbon is prepared via a “killing two birds with one stone” strategy.•The LC-750 exhibits superior pore structures and high graphitization degree.•The LC-750 cathode shows high capacity and excellent performance in AZICs.•The N and S incorporation enhances the Zn2+ adsorption ability and charge transfer behavior. Emerging aqueous zinc–ion hybrid capacitors (AZICs) are considered a promising energy storage because of their superior electrochemical performance. The pore structure, suitable heteroatom content, and graphitization degree (GD) of carbon-based cathodes significantly influence the electrochemical performance of AZICs. The N, S dual-doped porous graphitic carbon materials (LC-750) with the combined characteristics of high GD (1.11) and large specific surface area (1678.38 m2 g−1) are successfully developed by a facile “killing two birds with one stone” strategy using K3Fe(C2O4)3·3H2O as the activating and graphitizing agent, and waste sponge (WS) and coal tar pitch (CTP) as the heteroatom and carbon resource, respectively. Results show that the LC-750 cathode displays high capacities of 185.3 and 95.2 mAh g−1 at 0.2 and 10 A g−1. Specifically, the assembled LC-750//Zn capacitor can offer a maximal energy density of 119.5 Wh kg−1, a power density of 20.3 kW kg−1, and a capacity retention of 87.8% after 15,000 cycles at 10 A g−1. Density functional theory simulations demonstrate that N and S dual-doping can promote the adsorption kinetics of Zn ions. This design strategy is a feasible and cost-effective method for the preparation of dual heteroatom-doped graphitic carbon electrodes, which enables recycling of WS and CTP into high-valued products.